Does Perceptual Learning Style Matching Affect L2 Incidental Vocabulary Acquisition through Reading? - Hatami, Sarvenaz (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée, 2018)
Learning style matching is a neglected factor that may affect the complex process of second language (L2) incidental vocabulary acquisition through reading. The purpose of the current study is to investigate whether there is any difference in L2 incidental vocabulary acquisition and retention through reading when learners’ perceptual learning style is matched to their input mode, mismatched to their input mode, or mixed. The participants were 108 Iranian English as a foreign language (EFL) learners at pre-intermediate levels of English proficiency. Based on their perceptual learning style preferences (visual, auditory, kinaesthetic/tactile, mixed), they were divided into a reading group (consisting of three subgroups: Matched, Mismatched, Mixed) and a control group. The reading group read a graded reader containing 16 target words and then completed immediate and delayed (3 weeks later) vocabulary post-tests. The results revealed no significant differences between the three reading subgroups in terms of incidental vocabulary acquisition and retention. The findings suggest that perceptual learning style matching has no benefits for incidental word learning through reading.